Trends in Antibiotic Use in a Large Children's Hospital in London (United Kingdom): 5 Years of Point Prevalence Surveys - Kevin Meesters; Faye Chappell; Alicia Demirjian (MDPI AG, 2024)
Background: Antibiotics are commonly prescribed in paediatrics. As their excessive use contributes to adverse drug events, increased healthcare costs, and antimicrobial resistance, antimicrobial stewardship initiatives are essential to optimising medical care. These single-centre point prevalence surveys aimed to provide insights into antibiotic prescribing trends and identify targets for paediatric AMS activities. Methods: 14 point prevalence surveys were conducted from March 2016-April 2021, collecting data on antibiotic prescriptions, indication, adherence to guidelines, and route of administration. The UK adapted the World Health Organisation's AWaRe classification-guided antibiotic categorization. Results: 32.5% of all inpatients were on at least one antimicrobial; this remained stable during all surveys (range: 20-44%, p = 0.448). Of all prescriptions, 67.2% had an end- or review-date, and the majority was for agents in the Watch category (46.8-70.5%). Amoxicillin and clavulanate were the most frequently prescribed antibiotics (20.8%), followed by gentamicin (15.3%). Approximately 28.8% of all prescriptions were for prophylactic indications, while 7.6% of the prescriptions were not adherent to the hospital guidelines. Conclusions: This study highlights the importance of ongoing monitoring and robust AMS initiatives to ensure prudent antibiotic prescribing in paediatric healthcare. It underscores the need for tailored guidelines, educational efforts, and targeted interventions to enhance the quality of antibiotic usage, ultimately benefiting both individual patients and public health.